Subversion of Phytomyxae Cell Communication With Surrounding Environment to Control Soilborne Diseases; A Case Study of Cytosolic Ca2+ Signal Disruption in Zoospores of Spongospora subterranea - Amponsah, Jonathan; Tegg, Robert S.; Thangavel, Tamilarasan; Wilson, Calum R. (Frontiers in Microbiology, 2022)
Ca2+ signalling regulates physiological processes including chemotaxis in eukaryotes and prokaryotes. Its inhibition has formed the basis for control of human disease but remains largely unexplored for plant disease. This study investigated the role of Ca2+ signalling on motility and chemotaxis of Spongospora subterranea zoospores, responsible for root infections leading to potato root and tuber disease. Cytosolic Ca2+ flux inhibition with Ca2+ antagonists were found to alter zoospore swimming patterns and constrain zoospore chemotaxis, root attachment and zoosporangia infection. LaCl3 and GdCl3, both Ca2+ channel blockers, at concentrations ≥ 50 µM showed complete inhibition of zoospore chemotaxis, root attachment and zoosporangia root infection. The Ca2+ chelator EGTA, showed efficient chemotaxis inhibition but had relatively less effect on root attachment. Conversely the calmodulin antagonist trifluoperazine had lesser effect on zoospore chemotaxis but showed strong inhibition of zoospore root attachment. As expected, zoospore attachment was directly associated with root infection and zoosporangia development. High concentrations of extracellular Ca2+ (supplied as Ca(OH)2) had similar chemotaxis inhibitory effects and impairment of swimming pattern as the Ca2+ antagonists. These results highlight the fundamental role of Ca2+ signalling in zoospore chemotaxis and disease establishment. Their efficient interruption may provide durable and practical control of Phytomyxea soilborne diseases in the field .